Relieving Chronic Musculoskeletal Pain in Older Adults Using Transcranial Direct Current Stimulation: Effects on Pain Intensity, Quality, and Pain-Related Outcomes - Harvey, Marie-Philippe; Martel, Marylie; Houde, Francis; Daguet, Inès; Riesco, Eléonor; Léonard, Guillaume (Frontiers in Pain Research, 2022)
Introduction: Chronic pain is a significant health problem and is particularly prevalent amongst the elderly. Transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation technique that has been proposed to reduce chronic pain. The aim of this study was to evaluate and compare the efficacy of active and sham tDCS in reducing pain in older individuals living with chronic musculoskeletal pain. Materials and methods: Twenty-four older individuals (mean age: 68 ± 7 years) suffering from chronic musculoskeletal pain were randomized to receive either anodal tDCS over the contralateral motor cortex (2 mA, 20 minutes; n = 12), or sham tDCS (n = 12), for 5 consecutive days. Pain logbooks were used to measure pain intensity. Questionnaires (McGill Pain Questionnaire, Brief Pain Inventory, Beck Depression Inventory, Beck Anxiety Inventory, Pain Catastrophizing Scale, Margolis Pain Drawing and Scoring System [MPDSS]) were also used to assess pain in its globality. Results: Analysis of pain logbooks revealed that active tDCS led to a reduction in daily average pain intensity (all p ≤ 0.04), while sham tDCS did not produce any change (p = 0.15). Active tDCS also improved scores of all questionnaires (all p-values ≤ 0.02), while sham tDCS only reduced MPDSS scores (p = 0.04). Conclusions: These results suggest that anodal tDCS applied over the primary motor cortex is an effective modality to decrease pain in older individuals. tDCS can also improve other key outcomes such as physical and emotional functioning, and catastrophic thinking.